The Tragedy of the Self - Sangiacomo, Andrea (Open textbook library., 2023)
Why do human beings interpret their overall experience in terms of selfhood? How was the notion and sense of self shaped at different times and in different cultures? What sort of problems or paradoxes did these constructions face? These lectures address these and related questions by sketching a roadmap of possible theoretical avenues for conceiving of the self, bringing to the foreground its soteriological implications, while also testing this theoretical outlook against insights offered by various disciplines. Exploring the cross-cultural spectrum of possible ways of conceiving of the self invites the more existential question of whether any of these possibilities might offer resources for dealing with the tragedies of today’s world, or maybe even saving it from some of them.